Enhancing input to improve Hanoi College of Electronics and Electro-refrigeratory Technics non-English major students' speaking performance - Nguyễn, Hồng Hạnh (ĐHNN, 2017)
The first part is an introduction to the thesis which presents the factors as plan of the study such as the rationale, aims, scope, methods, research questions and design of the study. The second part presents a theoretical background, research methods, presentation of the data, data analysis and discussions. The final part focuses on the conclusions of the study, its limitations, recommendations and suggestions for further study.